2023
DOI: 10.3389/fcimb.2023.1146000
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of heterologous substrates by bacterial secretion systems for transkingdom translocation

Abstract: Bacterial secretion systems mediate the selective exchange of macromolecules between bacteria and their environment, playing a pivotal role in processes such as horizontal gene transfer or virulence. Among the different families of secretion systems, Type III, IV and VI (T3SS, T4SS and T6SS) share the ability to inject their substrates into human cells, opening up the possibility of using them as customized injectors. For this to happen, it is necessary to understand how substrates are recruited and to be able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 218 publications
0
3
0
Order By: Relevance
“…1B ). This is a relevant hypothesis considering that cytoplasmic substrates of the T4SS are known to interact with various T4SS subcomplexes along the secretion pathway (Cascales and Christie, 2004a ; Atmakuri et al, 2004 ; Cascales and Christie, 2004b ; Guzmán-Herrador et al, 2023 ). To address this question, we deleted the genes coding for several X-T4SS subunits that are associated with the bacterial inner membrane (VirB4, VirB6, VirB8, and VirD4) (Macé et al, 2022 ; Llosa et al, 2003 ), the outer membrane (VirB7, VirB9, and VirB10) (Fronzes et al, 2009 ; Chandran et al, 2009 ; Souza et al, 2011 ; Oliveira et al, 2016 ; Sgro et al, 2018 ) and the VirB5 subunit believed to form part of the extracellular pilus (Alvarez-Martinez and Christie, 2009 ; Christie et al, 2014 ; Sheedlo et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…1B ). This is a relevant hypothesis considering that cytoplasmic substrates of the T4SS are known to interact with various T4SS subcomplexes along the secretion pathway (Cascales and Christie, 2004a ; Atmakuri et al, 2004 ; Cascales and Christie, 2004b ; Guzmán-Herrador et al, 2023 ). To address this question, we deleted the genes coding for several X-T4SS subunits that are associated with the bacterial inner membrane (VirB4, VirB6, VirB8, and VirD4) (Macé et al, 2022 ; Llosa et al, 2003 ), the outer membrane (VirB7, VirB9, and VirB10) (Fronzes et al, 2009 ; Chandran et al, 2009 ; Souza et al, 2011 ; Oliveira et al, 2016 ; Sgro et al, 2018 ) and the VirB5 subunit believed to form part of the extracellular pilus (Alvarez-Martinez and Christie, 2009 ; Christie et al, 2014 ; Sheedlo et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This translocation is achieved by passing through the T3SS apparatus, a syringe-like structure, anchored within the bacterial membranes, with a long extracellular needle that extends toward the host cell membrane. It was previously demonstrated that EPEC, like other T3SS-containing bacteria, can deliver heterologous proteins into diverse cell types [18][19][20][21][22] or secrete them to the culture medium [23][24][25][26][27]. Most of these proteins were reporter proteins, facilitating the study of bacterial translocation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…To release DNA into the external environment, the gonococcus uses a type IV secretion system (T4SS) encoded by the genes of the gonococcal genetic island (GGI). In general, T4SSs are widespread in both Gram-positive and Gram-negative microorganisms and are subdivided into three families according to their biological functions [ 7 ]: (1) DNA conjugation, (2) protein transfer to a recipient cell (direct contact with the recipient cell is required), and (3) DNA secretion into the external environment (no contact with the cell is required). The gonococcal T4SS belongs to the latter family and releases single-stranded DNA into the medium in a contact-independent manner [ 8 ].…”
Section: Introductionmentioning
confidence: 99%